2015
DOI: 10.21608/jpp.2015.49321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic and Fulvic Acids With Some Nutrients at Diffrenet Time of Application on Yield and Fruits Quality of Anna Apple Trees

Abstract: The present investigation was undertaken during the selected two successive seasons of 2012 and 2013 on 12 years old Anna apple trees (Malus domestica, Borkh) budded on Shobra khan apple rootstocks. The selected trees were planted in a private orchard in Tanta, Gharbia Governorate, in clay soil and spaced at 3 x 4 meters apart. The trees were trained as open-vase form, irrigated by Nile water using surface irrigation (basing irrigation) system. The selected trees received the same horticultural practices and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The obtained results are in accordance with those of El-Kosary et al (2011) on Keitt and Ewais mango cultivars, they indicated that spraying microelements containing zinc and boron combined with amino and Humic acids improved weight, height, width, size, firmness of Keitt and Ewais mango fruits. In this concern, El-Boray et al, (2015) with Anna apple trees, they found that foliar application of mixture of calcium nitrate , zinc sulphate borax and humic or fulvic acids after fruit set increased the values of fruit height, fruit width, fruit weight and fruit volume.…”
Section: The Effect Of Calcium Zinc Boron and Its Combinations On Fmentioning
confidence: 97%
“…The obtained results are in accordance with those of El-Kosary et al (2011) on Keitt and Ewais mango cultivars, they indicated that spraying microelements containing zinc and boron combined with amino and Humic acids improved weight, height, width, size, firmness of Keitt and Ewais mango fruits. In this concern, El-Boray et al, (2015) with Anna apple trees, they found that foliar application of mixture of calcium nitrate , zinc sulphate borax and humic or fulvic acids after fruit set increased the values of fruit height, fruit width, fruit weight and fruit volume.…”
Section: The Effect Of Calcium Zinc Boron and Its Combinations On Fmentioning
confidence: 97%
“…The indirect impacts contain the factors which participate in providing energy for helpful organisms, influence the water holding capacity, impact the structure of the soil, distribution of various nutrients from minerals, enhance the trace minerals accessibility, and increase soil’s fertility. The changes which occurred in plant metabolism following the uptake of organic microelements, such as fulvic acid are considered a direct effect that include the entrance of these substances to plant cells and results in some biochemical changes in cytoplasmic components and membranes of cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of fertilisation treatments did not have significant effect on the average weight of strawberries. The authors of other experiments on the use of biostimulants, including humic acids, observed their positive effect on the weight of not only strawberries [45] but also apples [46,47]. However, the experiments conducted by Soldaniband et al [36] did not reveal any significant effect of the biostimulants on the weight of strawberries.…”
Section: Strawberry Fruit Qualitymentioning
confidence: 96%